The Effect of Cognitive Conflict Strategy on Improving Understanding of Students' Physics Concepts Reviewing from Cognitive Style - Ahmad Busyairi; Muh Makhrus; Ni Nyoman Sri Putu Verawati (Jurnal Ilmiah Profesi Pendidikan, 2022)
This study aims to determine the extent of the influence of cognitive conflict strategies on students' conceptual understanding in terms of cognitive style. This research is a quasi-experimental with one group pretest-posttest design. The sample used in the research consisted of 28 students who were studying at one of the universities in the city of Mataram. There are two main instruments used in this study, (1) the concept understanding test and (2) the Group Embedded Figure Test (GEFT). Concept understanding tests are given before and after treatment, while GEFT is only before treatment. The test result data was then analyzed using the N-Gain calculation. The results of data analysis showed that the average creativity of physics teacher candidates increased in the moderate category (N-Gain = 0.52). Students who have FD (filed dependence) cognitive style get a higher average N-gain score (N-Gain = 0.57) when compared to students who have FI (filed independence) learning style (N-Gain = 0.48). Based on the results of the effect size calculation, it shows that the effect of differences in cognitive style on increasing students' conceptual understanding is in the medium category.